Risk factors and familial clustering for fever 7–10 days after the first dose of measles vaccines. Issue 12 (14th March 2017) - Klein, Nicola P.; Lewis, Edwin; McDonald, Julia; Fireman, Bruce; Naleway, Allison; Glanz, Jason; Jackson, Lisa A.; Donahue, James G.; Jacobsen, Steven J.; Weintraub, Eric; Baxter, Roger
Highlights: Predictors of fever after MCV include MMRV, past fevers, past seizure, >3 visits. Fever after MCV clustered in families, after adjustment for care-seeking behavior. Suggests that some fevers after measles vaccines are related to genetic factors. Abstract: Background: Seven to ten days after a first dose of a measles-containing vaccine (MCV; i.e., MMR or MMRV), children have elevated fever risk which can be associated with febrile seizures. This study investigated individual and familial factors associated with fever 7–10 days after MCV. Methods: Retrospective cohort study among children who were <36 months of age at receipt of MCV in six sites of the Vaccine Safety Datalink from 1/1/2000 to 12/31/2012. We evaluated medically-attended clinic or emergency department visits with a code for fever 7–10 days after any MCV ("MCV- associated"). We evaluated factors associated with MCV-associated fever using χ 2 and multivariable logistic regression analyses. Results: Among 946, 806 children vaccinated with MCV, we identified 7480 (0.8%) MCV-associated fever visits. Compared with children without fever after MCV, children with MCV-associated fever were more likely to have received MMRV than MMR (OR 1.3 95% CI 1.2, 1.5), have had medically attended fever both following previous vaccines (OR 1.3 95% CI 1.1, 1.6) and at any other previous time (OR 1.7 95% CI 1.6, 1.8), have had at least 1 prior seizure (OR 2.2 95% CI 1.7, 2.7), and have had >3 medical visits within the 6 months before MCV (OR 1.7 95% CI 1.6, 1.8). In families with multiple MCV-immunized children, after adjusting for healthcare seeking behavior care for fever, those whose siblings had MCV-associated fever were more likely to also have MCV-associated fever (OR 3.5 95% CI 2.5, 4.8). Discussion: Children who received MMRV vaccine or who had prior medically-attended fevers and seizures during the first year of life had increased risk of fever after a first dose of measles vaccine. After adjusting for familial propensity to seek care, MCV-associated fever still clustered within families, suggesting a possible genetic basis for susceptibility to developing fever due to measles vaccines.